Clinical Uptake of Antimicrobial Stewardship Recommendations Following Nanosphere Verigene Blood Culture Gram-Negative Reporting. Issue 4 (1st October 2017) - Belknap, Aaron; Grosser, Daniel S.; Hale, Daniel A.; Lang, Benjamin J.; Colley, Peter; Benavides, Raul; Dhiman, Neelam
Abstract : We performed a retrospective chart review of patients to determine if the Verigene Gram-negative blood culture (BC-GN) results would lead to earlier deescalation of empiric therapy for inpatients with GN bacteremia with Citrobacter spp., Enterobacter spp., Klebsiella spp., and Escherichia coli to appropriate targeted coverage. A total of 899 records were reviewed from April 2014 to February 2016 from three institutions within the Baylor Scott & White Health network. The cases were reviewed for initial antibiotic coverage, timing of Verigene results, change in antibiotic coverage, and how these changes related to the timing of Verigene results. The lab reported the BC-GN results and final conventional susceptibility results within 2.5 ± 1.3 and 73.6 ± 40.0 hours from the Gram stain, respectively. Overall, 29.1% of patients were transitioned from empiric to targeted therapy at 12.2 ± 13.5 hours in response to BC-GN results, which was significantly earlier ( P < 0.001) than results by conventional methods. After accounting for patients already on targeted therapy, polymicrobial infections, and patients deceased or lost to follow-up, we identified antibiotic stewardship opportunities in −28% of GN infections. Further subanalysis demonstrated site-specific differences in the uptake of stewardship recommendations, whereby 32.4%, 50.5%, and 15.0% of cases at different hospitals demonstrated the expected change in antibiotics. These results suggest that Verigene had the expected impact in a third of the cases and the results reporting algorithm minimized the real-time involvement of the pharmacist while maintaining optimal patient management. However, this impact varied substantially by clinical site and was tempered by variable initial antibiotic coverage and clinician response.